Penerapan Metode RAD (Rapid Application Development) Dalam Perancangan Website Pemesanan Jasa Fotografi Joypotrait - Ardiyanto, Yusuf; Priyanto, Adhi; Puryono, Daniel Alfa (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Current technological developments require various types of businesses to be able to remain competitive and compete in the era of the digital world. Competitive companies need to innovate to add and find new customers and markets so that their business can survive and continue to develop well. One way companies can look for market opportunities through digital world platforms is by creating interactive websites. One business sector that can utilize websites to increase marketing reach is photography. Photo business owners can create a website that contains their photo portfolio, containing photos that will make many people interested in hiring a photography service package. Joypotrait as one of the photography service companies took the initiative not only to design a website for renting photography services, but also to provide additional features to attract customers in the form of access to buying and selling transactions of photos taken or documentation from Joypotrait itself which can be according to your wishes/needs or by requesting photos for customers. Photo orders based on requests from registered customers or with member status can be in the form of documentary photos with themes or objects that can be determined or chosen by themselves, for example natural panoramas, flora and fauna, automotive, profiles and so on. This website was designed using the RAD (Rapid Application Development) method which is divided into several stages, including; analyzing website needs, designing/designing websites, and implementing